Penerapan Sistem Administrasi pada Perum BULOG - Pratiwi, Nadya; Putri, Alivia Maharani (Insan Kreasi Media, 2024)
Along with the development of companies and demands for efficiency in the business world, the administration system has become a crucial aspect in maintaining the smooth running of company operations. Administration plays a central role in ensuring that a company can operate effectively and efficiently. Perum Bulog has an important role in maintaining national food security. Therefore, this activity aims to analyze the implementation of the administration system. This research uses the service-learning method, where the author applies his academic knowledge directly in work practice in the field. Activities include marketing planning and operations, preparing marketing collaborations, and promotions with other parties. The results of this activity include a deeper understanding of the administrative system at Perum Bulog through the application of theoretical concepts to real situations. The author successfully carried out Marketing and Customer Relations, Market Operations, administrative recaps, and stock opnam activities, which contributed to the company's operational effectiveness. The implication of this research is that the application of service learning in analyzing the administrative system at Perum Bulog can help improve the efficiency and effectiveness of company operations and support the goal of maintaining national food security freely. Providing valuable experience in applying knowledge and skills from education to the real world of work. This includes time discipline, teamwork, responsibility, and an understanding of marketing management and administration. Activities such as Market Operations, administrative recaps, and stock-taking provide in-depth insight into the work environment of the food logistics industry.